Amyloid of Rnq1p, the basis of the [PIN(+)] prion, has a parallel in-register β-sheet structure - Wickner, Reed B. (National Academy of Sciences, 2008)
The [PIN(+)] prion, a self-propagating amyloid form of Rnq1p, increases the frequency with which the [PSI(+)] or [URE3] prions arise de novo. Like the prion domains of Sup35p and Ure2p, Rnq1p is rich in N and Q residues, but rnq1Δ strains have no known phenotype except for inability to propagate the [PIN(+)] prion. We used solid-state NMR methods to examine amyloid formed in vitro from recombinant Rnq1 prion domain (residues 153–405) labeled with Tyr-1–(13)C (14 residues), Leu-1–(13)C (7 residues), or Ala-3–(13)C (13 residues). The carbonyl chemical shifts indicate that most Tyr and Leu residues are in β-sheet conformation. Experiments designed to measure the distance from each labeled residue to the next nearest labeled carbonyl showed that almost all Tyr and Leu carbonyl carbon atoms were ≈0.5 nm from the next nearest Tyr and Leu residues, respectively. This result indicates that the Rnq1 prion domain forms amyloid consisting of parallel β-strands that are either in register or are at most one amino acid out of register. Similar experiments with Ala-3–(13)C indicate that the β-strands are indeed in-register. The parallel in-register structure, now demonstrated for each of the yeast prions, explains the faithful templating of prion strains, and suggests as well a mechanism for the rare hetero-priming that is [PIN(+)]'s defining characteristic.